Onset and remission of rhinitis among students in relation to the home and school environment—A cohort study from Northern China. (6th May 2019) - Norback, Dan; Li, Tian; Bai, Xu; Li, Chenghuan; Zhao, Zhuohui; Zhang, Xin
Abstract: Few prospective studies exist on indoor and outdoor air pollution in relation to adolescent rhinitis. We studied associations between onset and remission of rhinitis among junior high school students in relation to the home and school environment. A 2‐year questionnaire cohort study was performed among 1325 students (11‐15 years) in eight schools in Taiyuan, Northern China. Climate and air pollution were measured by direct reading instruments and passive samplers inside and outside the schools at baseline. Associations were calculated by multilevel logistic regression. Two‐year onset of rhinitis and weekly rhinitis were 26.7% and 13.1%, respectively. RH ( P  < 0.001), CO2 ( P  < 0.01) and PM10 ( P  < 0.01) in the classrooms, PM10 ( P  < 0.01) and NO2 ( P  < 0.05) outside the schools, and redecoration (OR = 2.25) and dampness/indoor mold at home (OR = 2.04) were associated with onset of weekly rhinitis. RH ( P  < 0.05) and CO2 ( P  < 0.05) in the classroom and dampness/indoor mold (OR = 0.67) and environmental tobacco smoke (ETS) at home (OR = 0.63) reduced remission of rhinitis. In conclusion, dampness/mold and chemical emissions from new materials at home can increase onset of rhinitis and ETS and dampness/mold can reduce the remission. PM10, RH, CO2, and NO2 at school can increase the onset, and RH and CO2 can reduce the remission of rhinitis.